Basic psychological needs satisfaction and fear of missing out: Friend support moderated the mediating effect of individual relative deprivation. (October 2018) - Xie, Xiaochun; Wang, Yuhui; Wang, Pengcheng; Zhao, Fengqing; Lei, Li
Highlights: BPNS is a protective factor for FOMO. Individual relative deprivation was a mediator in the relation. Social support from friends moderated the mediation effect. Abstract: Fear of missing out (FOMO) is a new mental illness in digital era. Basing on the self-determination theory, the present study investigated how basic psychological needs satisfaction reducing FOMO. We tested a moderated mediating model that friend support moderated the mediating role of individual relative deprivation on the relation between basic psychological needs satisfaction and FOMO. A sample of 815 college students (mean age = 19.03 ± 1.13 years) participated our paper-and-pencil survey. Results showed that, basic psychological needs satisfaction negatively correlated with FOMO, and it reduced participants' FOMO via reducing individual relative deprivation. What's more, the mediating effect was moderated by friend support, comparing with low friend support participants, the indirect effect was larger among high friend support participants. The present study indicated that basic psychological needs satisfaction, and friend support were protective factors for college students' mental health. The limitations and implications were discussed.